Marketing Strategy for Sabar Savings (Eid Savings) in Increasing the Number of Members at KSPPS BMT NU Leces Branch - Nurdian Nila Sari; Yeni Kartikawati (Formosa Journal of Applied Sciences, 2022)
KSPPS BMT NU Leces Branch is an Islamic financial institution that provides a variety of savings and financing products. One of the savings products at KSPPS BMT NU Leces Branch is the SABAR Savings (Eid savings) where this patient savings is provided for customers who are interested in saving for the needs of the holidays. The aim of this research is to analyze the marketing strategy of Lebaran Savings Savings (SABAR) in increasing members at KSPPS BMT NU Leces Branch. ) In Increasing Members at KSPPS BMT NU Leces Branch, the results of the study show that the marketing strategy for SABAR savings at KSPPS BMT NU Leces branch first looks at the situation, so they know the steps in marketing their products.